Children and adolescents with sickle cell disease: characteristics and use of medicinal plants - Rebeca Garcia de Paula; Hewerthon Medrado Ribeiro; Luciana de Melo Borges; Lucas Barbosa e Souza; Kellen Lagares Ferreira Silva; Carla Simone Seibert (Sociedade de Pediatria de São Paulo, 2024)
ABSTRACT Objective: The aim of this study was to describe the epidemiological characteristics of pediatric patients with sickle cell disease (SCD) and evaluate the use of medicinal plants in these patients concomitantly with their drug treatment. Methods: This is a review of the medical records of pediatric patients at a public institution with tertiary care. The selection criterion was to be a child or adolescent with SCD undergoing pediatric follow-up at this outpatient clinic. In the medical records of the patients selected, records of the use of plants for medicinal purposes were sought. Results: In total, 154 records (100% of total active patients followed in this clinic) were reviewed: 99 children and 55 adolescents. The predominant genotype was SS (58.4%), followed by SC (29.2%). The use of at least one medication for SCD was reported in 95.5% of the medical records. The use of medicinal plants was reported by 70.1% of patients, with 276 citations in the medical records referring to 64 different types of plants. Six plants were used for the treatment of SCD, the main one being Lemonvine/Ora-pro-nóbis (Pereskia aculeata). The use of medicinal plants was reported for flu-like symptoms and/or COVID-19 (both for prevention and treatment) by 60.5% of the citations, with 35 different plants reported for this use, exclusively or not. This use was followed by pain symptoms (14.2% of citations). Conclusions: The majority of patients in this study use both conventional and traditional/complementary/alternative medicine, highlighting the need for more studies in the area, with a special focus on patient safety.